Post-submergence Nitrogen Fertilizer Management for Enhancing Rainfed Lowland Rice Productivity in Eastern India - Behera, U. K.; Singh, Sudhanshu; Sarangi, Sukanta K.; Behera, S. K.; Bishoyi, B. S.; Srivastava, A. K.; Singh, U. S. (International Journal of Bio-resource and Stress Management, 2019)
Flashflood in rainfed lowlands seriously affect rice crop establishment and cause severe yield losses. Survival of new flood tolerant rice varieties (Swarna-Sub1, Samba Mahsuri-Sub1, IR64-Sub1, etc.) developed through introgressing the submergence tolerance gene SUB1into mega rice varieties of South Asia is substantially higher than that of non-Sub1 varieties under flooding stress. This has been consistently reflected in a yield advantage of 1 to 3 t ha-1. Submergence tolerance and productivity of these Sub1 varieties can be further enhanced through adoption of appropriate crop and nutrient management practices. Post-flood nitrogen application plays an important role in helping rice plants to resume quick growth after flood water recession. On station experiments conducted during the wet seasons (Kharif) of 2011 and 2012 at the college of agriculture, Chiplima, Sambalpur, Odisha, to study the effect of 3 post-flood nitrogen doses (N1: 10 kg ha-1; N2: 20 kg ha-1; N3: 30 kg ha-1) and 3 application times (% plants started showing at least one green leaf after de-submergence) viz. T1: 10-15%; T2: 30-35% and T3: 65-70% on survival, growth and yield performance of the rice variety Swarna-Sub1. Treatments N3 (91.4%) and T2 (96.3%) produced significantly higher survival than other treatments. Additional N increased the yield attributes and finally grain yield. Mean maximum grain yield was recorded with N3 (3485 kg ha-1) and T2 (3623 kg ha-1). When the additional N dose was applied earlier (T1) or late (T3), the average yield reduction was 19 and 12%, respectively, compared to T2.